High Tunability and Low Loss in Layered Perovskite Dielectrics through Intrinsic Elimination of Oxygen Vacancies - Zhang, Hangfeng; Gidden, Henry; Saunders, Theo Graves; Liu, Ning; Aurallo-Peters, Vicente; Xu, Xinzhao; Palma, Matteo; Reece, Michael John; Abrahams, Isaac; Yan, Haixue; Hao, Yang (Chemistry of materials, 2020)
Dielectric materials with moderate dielectric permittivity, high tunability, and low loss are critical in modern communication technology. However, high tunability is often associated with high loss and high dielectric permittivity. Here, a novel material, textured Sr2(Ta1–x Nb x )2O7 (STN), with a layered perovskite structure, has been designed to break this correlation. These materials exhibit low dielectric loss associated with oxygen vacancy elimination through the creation of stacking faults in the layered structure, as evidenced by transmission electron microscopy (TEM). A modification of the Vendik model was used to fit the thermal dependence of their relative dielectric permittivity, which included an oxygen defect parameter as an indicator of the oxygen defect concentration. The high tunability is attributed to the presence of local polar nanoclusters just above the Curie point. A two-step spark plasma sintering method was employed to prepare grain-oriented ceramics with optimized properties. A near-optimum maximum tunability of 72% at room temperature was obtained for a textured Sr2Ta1.88Nb0.12O7 ceramic, with moderate dielectric permittivity (ε′ ∼ 520) and a dielectric loss of less than 1%.